Efficient market and the COVID-19 pandemic: Case of ASEAN-5 - Winston Pontoh; Novi Swandari Budiarso (The Contrarian : Finance, Accounting, and Business Research, 2022)
The issue of Covid-19 has a negative impact, especially on the capital markets of ASEAN-5 countries (Indonesia, Malaysia, Singapore, Thailand, and the Philippines). This study aims to examine the movement of market returns in ASEAN-5 countries at the start of the Covid-19 pandemic. The data used are daily market indices for the period 2020 to 2021. The findings show that market indices for all ASEAN-5 countries move unstable throughout 2020. In 2021, efficient market conditions under the assumption of a weak form only occur in Singapore where the trend of the index of the market becomes more predictable. Empirical evidence also shows that the interrelationship between market indices in ASEAN-5 countries is varied.